Therapeutic Potential of TLR8 Agonist GS‐9688 (Selgantolimod) in Chronic Hepatitis B: Remodeling of Antiviral and Regulatory Mediators. Issue 1 (20th June 2021) - Amin, Oliver E.; Colbeck, Emily J.; Daffis, Stephane; Khan, Shahzada; Ramakrishnan, Dhivya; Pattabiraman, Divya; Chu, Ruth; Micolochick Steuer, Holly; Lehar, Sophie; Peiser, Leanne; Palazzo, Adam; Frey, Christian; et al.
Abstract : Background and Aims: GS‐9688 (selgantolimod) is a toll‐like receptor 8 agonist in clinical development for the treatment of chronic hepatitis B (CHB). Antiviral activity of GS‐9688 has previously been evaluated in vitro in HBV‐infected hepatocytes and in vivo in the woodchuck model of CHB. Here we evaluated the potential of GS‐9688 to boost responses contributing to viral control and to modulate regulatory mediators. Approach and Results: We characterized the effect of GS‐9688 on immune cell subsets in vitro in peripheral blood mononuclear cells of healthy controls and patients with CHB. GS‐9688 activated dendritic cells and mononuclear phagocytes to produce IL‐12 and other immunomodulatory mediators, inducing a comparable cytokine profile in healthy controls and patients with CHB. GS‐9688 increased the frequency of activated natural killer (NK) cells, mucosal‐associated invariant T cells, CD4 + follicular helper T cells, and, in about 50% of patients, HBV‐specific CD8 + T cells expressing interferon‐γ. Moreover, in vitro stimulation with GS‐9688 induced NK‐cell expression of interferon‐γ and TNF‐α, and promoted hepatocyte lysis. We also assessed whether GS‐9688 inhibited immunosuppressive cell subsets that might enhance antiviral efficacy. Stimulation with GS‐9688 reduced the frequency of CD4 + regulatory T cells and monocytic myeloid‐derived suppressor cells (MDSCs). Residual MDSCs expressed higher levels of negative immune regulators, galectin‐9 and programmed death‐ligand 1. Conversely, GS‐9688 induced an expansion of immunoregulatory TNF‐related apoptosis‐inducing ligand + NK cells and degranulation of arginase‐I + polymorphonuclear MDSCs. Conclusions: GS‐9688 induces cytokines in human peripheral blood mononuclear cells that are able to activate antiviral effector function by multiple immune mediators (HBV‐specific CD8 + T cells, CD4 + follicular helper T cells, NK cells, and mucosal‐associated invariant T cells). Although reducing the frequency of some immunoregulatory subsets, it enhances the immunosuppressive potential of others, highlighting potential biomarkers and immunotherapeutic targets to optimize the antiviral efficacy of GS‐9688.